2008
DOI: 10.2147/btt.s3415
|View full text |Cite
|
Sign up to set email alerts
|

Lepirudin in the management of patients with heparin-induced thrombocytopenia

Abstract: Lepirudin, a recombinant hirudin, is a direct irreversible thrombin inhibitor by binding to both free and clot-bound thrombin. It is approved for treatment of heparin-induced thrombocytopenia (HIT), which is a serious antibody-mediated drug reaction mostly associated with the use of unfractionated heparin. Clinical experience during the last 10 years has proved the efficacy of lepirudin in the management of HIT. The major route of elimination of lepirudin is the kidney, accounting for approximately 90% of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…The anticoagulant drug lepirudin is excreted by the kidney with systemic clearance in women about 25% lower than in men (NDA 020807 [31]). But PK variables do not translate linearly into phenotypes; thus, in women lepirudin is detectible in the circulation for up to 48 h, compared to just 2 h in men, which greatly increases the potential for undesired bleeding [32]; indeed, in this example, low molecular weight heparin-induced thrombocytopenia is a clinically important ADR which occurs more frequently in women than men [33], a difference that corresponded to much higher drug exposure as indicated by female-bias in multiple PK measures.…”
Section: Reasons Why Men and Women Respond Differently To Drugsmentioning
confidence: 99%
“…The anticoagulant drug lepirudin is excreted by the kidney with systemic clearance in women about 25% lower than in men (NDA 020807 [31]). But PK variables do not translate linearly into phenotypes; thus, in women lepirudin is detectible in the circulation for up to 48 h, compared to just 2 h in men, which greatly increases the potential for undesired bleeding [32]; indeed, in this example, low molecular weight heparin-induced thrombocytopenia is a clinically important ADR which occurs more frequently in women than men [33], a difference that corresponded to much higher drug exposure as indicated by female-bias in multiple PK measures.…”
Section: Reasons Why Men and Women Respond Differently To Drugsmentioning
confidence: 99%
“…Peak plasma concentration occurs after 3-4 hours. Ninety percent of the administered dose of lepirudin is excreted through the kidneys [123].…”
Section: Lepirudinmentioning
confidence: 99%
“…In the absence of a known antidote or drug to reverse its effect, hemofiltration has been used to enhance the elimination of lepirudin at the end of CPB. 18 , 19 Although clinical trials have demonstrated its efficacy to provide anticoagulation, allergic reactions ranging from urticaria to hemodynamic instability have been reported. 20 , 21 These anaphylactoid reactions may occur regardless of previous exposure, although reexposure to lepirudin is associated with a greater risk when compared with first exposure.…”
Section: Discussionmentioning
confidence: 99%